2012
DOI: 10.1192/bjp.bp.111.096479
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-resistant and insufficiently treated depression and all-cause mortality following myocardial infarction

Abstract: All-cause mortality following an acute myocardial infarction is greatest in patients with depression who are insufficiently treated and is a risk in patients with treatment-resistant depression. However, the risk of mortality associated with treatment-resistant depression is partly explained by comorbid disorders. Further studies are warranted to determine whether changes in depression independently predict all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 16 publications
1
42
0
2
Order By: Relevance
“…(15) We followed a definition previously employed in retrospective cohort studies involving medical records. (16, 17) Patients were defined as having TRD if any of the following were recorded in the medical record: a) electroconvulsive therapy, b) MAOI prescription, c) two or more antidepressants (any SSRI, SNRI, TCA or “other” non-MAOI antidepressant) at the same time overlapping by at least 31 days, or d) augmentation therapy (i.e. prescription of a mood stabilizing or atypical antipsychotic after antidepressant treatment).…”
Section: Methodsmentioning
confidence: 99%
“…(15) We followed a definition previously employed in retrospective cohort studies involving medical records. (16, 17) Patients were defined as having TRD if any of the following were recorded in the medical record: a) electroconvulsive therapy, b) MAOI prescription, c) two or more antidepressants (any SSRI, SNRI, TCA or “other” non-MAOI antidepressant) at the same time overlapping by at least 31 days, or d) augmentation therapy (i.e. prescription of a mood stabilizing or atypical antipsychotic after antidepressant treatment).…”
Section: Methodsmentioning
confidence: 99%
“…It is evidenced that depression is common after coronary event [27] and it continues to remain under recognized and poorly treated in cardiac population [28]. Previous research has shown that ACS patients benefit from cognitive behavioural therapy following an episode of myocardial infarction [29] and therefore, measuring emotional status will assists clinicians to identify depressive symptoms.…”
Section: Discussion Principal Resultsmentioning
confidence: 99%
“…Scherrer and colleagues [81] found that post-MI patients with treatment-resistant depression had mortality intermediate between adequate treatment cases and inadequate treatment cases, but that they also had more co-morbid medical problems. They concluded that more research is necessary to determine whether changes in depression independently predict all-cause mortality.…”
Section: Future Prospectsmentioning
confidence: 97%